2006
DOI: 10.1113/jphysiol.2006.121558
|View full text |Cite
|
Sign up to set email alerts
|

Exercise pressor reflex function is altered in spontaneously hypertensive rats

Abstract: In hypertension, exercise elicits excessive elevations in mean arterial pressure (MAP) and heart rate (HR) increasing the risk for adverse cardiac events and stroke during physical activity. The exercise pressor reflex (a neural drive originating in skeletal muscle), central command (a neural drive originating in cortical brain centres) and the tonically active arterial baroreflex contribute importantly to cardiovascular control during exercise. Each of these inputs potentially mediates the heightened cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
88
3
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 44 publications
12
88
3
7
Order By: Relevance
“…One was 30-s continuous static contraction, commonly used to study the physiological roles of the exercise pressor reflex (19,20,37,38,43). Another was 1-min intermittent (1-4 s of stimulation to relaxation) static contraction.…”
Section: H148mentioning
confidence: 99%
See 1 more Smart Citation
“…One was 30-s continuous static contraction, commonly used to study the physiological roles of the exercise pressor reflex (19,20,37,38,43). Another was 1-min intermittent (1-4 s of stimulation to relaxation) static contraction.…”
Section: H148mentioning
confidence: 99%
“…This muscle-based reflex is termed the exercise pressor reflex (35). A series of studies by Smith and colleagues (24,37,38,43) using a decerebrate rat preparation has suggested that in spontaneous hypertensive rats (SHRs), both mechanically and chemically sensitive muscle afferents engaged during skeletal muscle contraction are stimulated excessively compared with those in normotensive rats, thereby evoking exaggerated sympathoexcitatory and pressor responses to contraction. In humans with hypertension, the elevation in muscle sympathetic nerve activity seen during postexercise ischemia, a maneuver that selectively excites chemically sensitive muscle afferents, was higher than that in normotensive subjects (10).…”
mentioning
confidence: 99%
“…4,18,19). Of these, recent evidence in both the animal and human literature suggests that the EPR contributes significantly to the abnormally accentuated circulatory response to exercise in hypertension (2,22,23,38). Activation of the EPR, a reflex originating in skeletal muscle, is mediated by stimulation of mechanically sensitive receptors located primarily on group III afferent fibers and metabolically sensitive receptors located primarily on group IV afferent fibers (10, 11).…”
mentioning
confidence: 99%
“…Activation of the EPR, a reflex originating in skeletal muscle, is mediated by stimulation of mechanically sensitive receptors located primarily on group III afferent fibers and metabolically sensitive receptors located primarily on group IV afferent fibers (10,11). In hypertension, combined or individual activation of either the mechanical (i.e., mechanoreflex) or metabolic component (i.e., metaboreflex) of the EPR results in a heightened sympathetically mediated cardiovascular response (2,13,22,23,34,38). To date, however, the mechanisms underlying EPR overactivity in hypertension remain largely unknown.…”
mentioning
confidence: 99%
“…First, Smith et al 84) showed that electrically induced continuous static muscle contraction reflexly elicited a greater pressor response in spontaneous hypertensive rats (SHRs) than that in normotensive controls, suggesting the exaggeration of the EPR in hypertension (Fig. 2).…”
Section: Contribution Of Rat Studies To Understanding Of Mechanisms Umentioning
confidence: 99%